2005
DOI: 10.1038/modpathol.3800328
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of endometrial carcinoma by subjective endometrial intraepithelial neoplasia diagnosis

Abstract: Endometrial intraepithelial neoplasia (also known as 'EIN') is a precursor to endometrioid endometrial adenocarcinoma characterized by monoclonal growth of mutated cells, a distinctive histopathologic appearance, and 45-fold elevated cancer risk. We have applied diagnostic criteria for EIN to 97 successive endometrial biopsies classified as hyperplastic according to World Health Organization criteria and correlated results with computer-assisted morphometry (D-score) and clinical cancer outcomes. Three patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
93
0
4

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(100 citation statements)
references
References 19 publications
(26 reference statements)
2
93
0
4
Order By: Relevance
“…For example, threshold functions applied to prostate histopathology may be conceived and elaborated. The 'D-score' histomorphometric qualitative threshold function, conceived to predict the progression of endometrial intraepithelial neoplasia to endometrial cancer, has shown enhanced predictive power as compared to alternate systems (73,74).…”
Section: Conclusion and Research Perspectivesmentioning
confidence: 99%
“…For example, threshold functions applied to prostate histopathology may be conceived and elaborated. The 'D-score' histomorphometric qualitative threshold function, conceived to predict the progression of endometrial intraepithelial neoplasia to endometrial cancer, has shown enhanced predictive power as compared to alternate systems (73,74).…”
Section: Conclusion and Research Perspectivesmentioning
confidence: 99%
“…It is noteworthy that large studies correlating endometrial biopsies and/or curettages with findings on close follow-up hysterectomy are to our knowledge lacking, but these data are now beginning to be reported. 8 Longacre et al eschewed the empiric approach and based their distinction of CAH from WDA on morphologic features that correlated retrospectively with myometrial invasion specifically, a clinically relevant "gold standard." 9 Using their criteria, myoinvasive carcinomas should be extraordinarily rare in hysterectomies after a diagnosis of CAH.…”
mentioning
confidence: 99%
“…It would be informative to redo the expert panel review segment of GOG Protocol 167 keeping in mind the importance of defining an adequate or representative sample using pathologists schooled in the approaches of Mutter, Baak, and Longacre. [5][6][7][8][9] If consensus was reached, I would propose devising training sessions to be followed by tests of interobserver agreement and feasibility. It would be a worthy challenge.…”
mentioning
confidence: 99%
“…Dadas las dificultades existentes para la categorización de la hiperplasia endometrial atípica o el adenocarcinoma, algunos autores han creado el concepto de neoplasia endometrial intraepitelial, que clasifica aparentemente de manera más eficaz a las pacientes con riesgo alto y bajo de cáncer y con mejor reproducibilidad que la hiperplasia endometrial atípica (9,15,16,17). Sin embargo, la OMS (5,6) aún mantiene la clasificación con base en la histopatología de presencia o no de atipia celular, que se resume en la Tabla I. Dicha clasificación es la que actualmente la mayoría de patólogos aún consideran describiendo estas lesiones intraepiteliales dentro del grupo de las hiperplasias atípicas (5,6,8,9,10,11,18,19).…”
Section: Introductionunclassified